Pengaruh Permainan Ular Tangga dan Buku Cerita Bergambar sebagai Media Promosi Kesehatan Terhadap Praktek Cuci Tangan Pakai Sabun - Fitriastuti, Enny Suci (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTThe Effect Of Game Snakes And Ladders Illustrated Book Stories As Media Of Health Promotion Toward The Practice Of Handwashing: Children are the group most vulnerable to the transmission of the disease. Morbidity of diarrhea in children aged 5-14 years in Pekalongan in 2013 as many as 6,014 or 21.6% of total patients with diarrhea. Transmission of the disease in children can be prevented by hand washing with soap (CTPS). Handwashing child can through health education. Media used in a variety of health education as a game of snakes and ladders and picture books. This study aims to determine the effectiveness of the game of snakes and ladders and picture books as a medium for health promotion against the practice of handwashing with soap in primary school students in the District Karanganyar Regency Pekalongan. Using a quasi-experimental research design. Samples were elementary school students grades 4 and 5 SDN Kayugeritan many as 46 people and SDN Kulu many as 46 people with purposive sampling technique. The instrument used was a game of snakes and ladders, picture books and hand-washing practices check list. Data analysis using the Mann Whitney.The results showed that there was a difference in effectiveness between the game of snakes and ladders and picture books as a medium for health promotion against the practice of handwashing with soap in primary school students in the District Karanganyar Pekalongan with value 0,000 <0,05. Snakes and ladders game media is more effective than a picture story book. Based on the research results it is recommended that the health institutions to improve health education about the practice of washing hands with soap and using health education media easy and interesting for children of elementary school students like snakes and ladders game media.Keywords: effectiveness, health education, snakes and ladders games, picture booksÂ